Faktor Resiko Cacingan Pada Anak Usia Sekolah Dasar - Masra, Ferizal; Barus, Linda; Indarwati, Suami (Universitas Malahayati Bandar Lampung, 2022)
Background: Worm disease is a disease caused by Soil Transmitted Helminth (STH) infection or intestinal worm parasitic infection that is transmitted through the soil. Worm parasites that often cause intestinal worms in Indonesia are roundworms (Ascaris lumbricoides), whipworms (Trichuris trichuria) and hookworms (Necator americanus and Ancylostoma duodenale). Worm disease is still a public health problem in developing countries like Indonesia, because of its high morbidity and mortality. More than 1.5 billion people, or 24% of the world's population, are infected with soil-borne helminths worldwide. Infection is widespread in tropical and subtropical regions, with the greatest number occurring in sub-Saharan Africa, America, China and East Asia. (WHO, 2022). The results of a survey by the Ministry of Health of the Republic of Indonesia from several provinces in Indonesia showed that the general worm prevalence was 40-60%. While the number of events increases to 30-90%, if the prevalence is calculated in school-age children. (Rosyidah & Prasetyo, 2018). The age range that often experiences worms is the age of 6-12 years or at the elementary school (SD) level because it is influenced by the level of personal hygiene. (Rahma et al., 2020; Suriani et al., 2019)Many factors play a role as risk factors for worms to occur, especially in elementary school-age children. (Amoah, 2018) states that Water, Sanitation and Hygiene (WASH) is the main risk factor for STH infection in humans, in addition to socioeconomic risk factors (poverty). Meanwhile, according to (Gabrie, 2013) the risk factors for worm infection are Host Biology Factor, Host Behavior Factor, Socio-Economic Factor, Environmental Factor, and Other Factors.Purpose: The aim of this study was to get an overview of the risk factors experienced by worms sufferers. The research was conducted in July-August 2022 in the Working Area of the Kelumbayan Induk Health Center, Tanggamus Regency.Method: This research was conducted using quantitative methods with a descriptive research design. The population and sample of this study were students in grades 1 to 6 at SDN 1 Kiluan Negeri, Kelumbayan District, Tanggamus Regency, where the population consisted of all 218 students (Dapodik Students at SDN 1 Kiluan Negeri). While the research sample consisted of 71 students who were selected using the Simple Random Sampling technique, and the determination of the sample size used the Slovin and Kotler formula. Data collection was carried out by observing for 1 week the presence of risk factors, both in the home environment, school environment, and other factors. The research results were processed and analyzed descriptively and presented using a frequency table to get an overview of the risk factors for helminthiasis in the Working Area of the Kelumbayan Induk Health Center, Tanggamus Regency in 2022Results: The results showed that 80.3% of the number of family members living in the same house was quite large, 21.1% of the respondents' houses had dirt floors, 2.8% of the respondents did not have a healthy family latrine, 5.6% of the respondents' houses did not have access to clean water, 88.7% raise livestock in the yard, 43.7% of respondents do not have the habit of washing hands with soap and running water, 36.6% still have the habit of not using footwear when playing outside, 39.4% respondents have games that come into contact with the ground, and 95.8% stated that they had consumed deworming medicationConclusion: The condition of the respondent's home environment and the respondent's habits are still at risk of causing transmission and spread of worms in the community. For this reason, it is necessary to increase the role of teachers in schools to pay even greater attention to students to always maintain personal hygiene and the cleanliness of their environment, and parents need to remind their children to always maintain personal hygiene, especially at home. Meanwhile, the Puskesmas is routinely monitoring the growth and development of elementary school-age children as well as carrying out continuous helminthiasis surveys accompanied by treatment efforts for children who are proven to have worms.Suggestion For parents to pay more attention to their children's health by checking them at a health facility, giving deworming medication to children who are positive for worms, and providing examples of proper hand washing. The school should make hand washing facilities so that students can practice the correct way of washing hands. To the puskesmas to reactivate the deworming program for elementary school childrenKeywords: Worms, Personal Hygiene, Elementary school age ABSTRAK Latar Belakang: Penyakit cacingan adala penyakit yang diakibatkan oleh infeksi Soil Transmitted Helminth (STH) atau infeksi parasit cacing usus yang penularan melalui tanah. Parasit cacing yang sering menyebabkan penyakit cacingan di Indonesia adalah cacing gelang (Ascaris lumbricoides), cacing cambuk (Trichuris trichuria) dan cacing tambang (Necator americanus dan Ancylostoma duodenale). Penyakit cacingan masih merupakan masalah kesehatan masyarakat di negara berkembang seperti di Indonesia, karena morbiditas dan mortalitas-nya yang masih tinggi. Lebih dari 1,5 miliar orang, atau 24% dari populasi dunia, terinfeksi cacing yang ditularkan melalui tanah di seluruh dunia. Infeksi tersebar luas di daerah tropis dan subtropis, dengan jumlah terbesar terjadi di sub-Sahara Afrika, Amerika, Cina dan Asia Timur.(WHO, 2022). Hasil survei Departemen Kesehatan Republik Indonesia dari beberapa provinsi di Indonesia didapatkan persentase kecacingan secara umum sebesar 40-60%. Sedangkan jumlah kejadian meningkat hingga 30-90%, jika prevalensi dihitung pada anak usia sekolah.(Rosyidah & Prasetyo, 2018). Rentang usia yang sering mengalami cacingan yaitu usia 6-12 tahun atau pada jenjang sekolah dasar (SD) karena dipengaruhi oleh tingkat personal hygiene. (Rahma et al., 2020; Suriani et al., 2019)Banyak faktor yang berperan sebagai faktor resiko terjadi cacingan, terutama pada anak usia sekolah dasar. (Amoah, 2018) menyatakan bahwa Air, Sanitasi dan Kebersihan (WASH) merupakan faktor resiko yang utama terjadinya infeksi STH pada manusia, selain faktor resiko sosial ekonomi (kemiskinan). Sedangkan menurut (Gabrie, 2013) faktor resiko terjadinya infeksi cacingan adalah Host Biology Factor, Host Behaviou Factor, Socio-Economic Factor, Environmental Factor, dan Other Factors.Tujuan: Penelitian bertujuan untuk mendapatkan gambaran faktor resiko yang dialami penderita cacingan. Penelitian dilaksanakan pada bulan Juli-Agustus tahun 2022 di Wilayah Kerja Puskesmas Kelumbayan Induk Kabupaten Tanggamus.Metode: Penelitiain ini dilakukan menggunakan metode kuantitatif dengan desain penelitian Deskriptif. Populasi dan sampel penelitian ini adalah siswa-siswi kelas 1 sampai 6 SDN 1 Kiluan Negeri Kecamatan Kelumbayan Kabupaten Tanggamus, dimana populasinya adalah seluruh siswa sebanyak 218 Siswa (Dapodik Siswa SDN 1 Kiluan Negeri). Sedangkan sampel penelitian adalah siswa yang terpilih dengan menggunakan teknik Simple Random Sampling berjumlah 71 orang, dan penentuan besar sampel menggunakan rumus Slovin and Kotler. Pengumpulan data dilakukan dengan cara observasi selama 1 minggu terhadap keberadaan faktor resiko, baik di lingkungan rumah lingkungan sekolah, dan faktor lainnya. Hasil penelitian diolah dan dianalisis secara deskriptif dan disajikan menggunakan tabel frekuensi untuk mendapatkan gambaran faktor resiko penyakit cacingan di Wilayah Kerja Puskesmas Kelumbayan Induk Kabupaten Tanggamus Tahun 2022Hasil: Hasil penelitian menunjukan bahwa 80,3% jumlah anggota keluarga yang tinggal serumah cukup besar, 21,1% rumah responden berlantai tanah, 2,8 % responden tidak memiliki jamban keluarga yang sehat, 5,6% rumah responden tidak memiliki akses ke air bersih, 88,7% memelihara hewan ternak di pekarang rumah, 43,7% responden tidak memiliki kebiasaan mencuci tangan dengan sabun dan air mengalir, 36,6% masih memiliki kebiasaan tidak menggunakan alas kaki saat bermain di luar, 39,4% responden memiliki permainan yang bersentuhan dengan tanah, dan 95,8% menyatakan pernah mengkonsumsi obat cacingKesimpulan: Kondisi lingkungan rumah responden dan kebiasaan responden masih banyak beresiko menimbulkan penularan dan penyebaran penyakit cacingan di masyarakat. Untuk itu perlu ditingkatkannya peran guru di sekolah untuk memberikan perhatian lebih besar lagi kepada anak didik untuk selalu menjaga kebersihan dirii dan kebersihan lingkungannya, dan pihak orang tua perlu harus mengingatkan anak-anaknya untuk selalu menjaga kebersihan diri terutama di rumah. Sedangkan pihak Puskesmas untuk rutin memantau tumbuh kembang anak-anak usia sekolah dasar sekaligus menjalankan melaksanakan survey kecacingan secara terus menerus disertai dengan upaya pengobatan buat anak-anak yang terbukti mengindap cacinganSaran Agar orang tua lebih memperhatikan kesehatan anaknya dengan memeriksakannya ke sarana kesehatan, memberikan obat cacing pada anak yang posif kecacingan, dan memberikan contoh mencuci tangan yang benar. Pada pihak sekolah agar membuat sarana cuci tangan agar siswa dapat mempraktekkan cara cuci tangan yang benar. Kepada pihak puskesmas agar mengaktifkan kembali program kecacingan pada anak sekolah dasar Kata Kunci: Cacingan, Personal Hygiene, Usia SD